Glucagon in Acute Medicine Pharmacological, clinical and therapeutic implications - Picazo, J. (Springer Netherlands, 1993)
An up-to-date account of the use of the gastrointestinal hormone glucagon in different clinical emergencies. An international group of experts from different fields of medicine cover a wide range of situations within acute medicine: cardiology, internal medicine, endocrinology, diabetology, clinical toxicology, surgery, paediatrics, gastroenterology, hepatology and radiology. Based on an Intenational Workshop held in Barcelona in October 1992, this volume, the fourth in the series, contributes to the growing interest in the importance of glucagon both as a diagnostic tool and as a therapeutic agent in acute medicine. It will be of value to physicians and emergency and critical care specialists as well as researchers interested in this fascinating hormone